Hawaiian Monk Seal ( Neomonachus schauinslandi ) Marine Debris Entanglement Risk Varies With Size Class and Sex - Jason D. Baker; Thea C. Johanos; Hope Ronco; Tracy A. Mercer; Brenda L. Becker (Marine Mammal Science, 2026)

Molecular epidemiology and evolution of norovirus in Australia and New Zealand, 2018 to 2020 - Grace J. H. Yan; Joanne Hewitt; Lewis K. Mercer; Emma F. Harding; Dawn Croucher; Alice G. Russo; Peter G. Huntington; Jason M. Mackenzie; William D. Rawlinson; Peter A. White (Infectious Diseases, 2025)

Distribution and disturbances of ditches across salt marshes of the Northeast U.S. with implications for management and restoration - Erin K. Peck; Julie E. Walker; Katherine V. Ackerman; Joel Carr; Maureen D. Correll; Zafer Defne; Linda A. Deegan; Mitchell J. Eaton; Neil K. Ganju; Mitch Hartley; Catherine Johnson; Jason Mercer; et al. (Journal of Environmental Management, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Sighting patterns reveal unobserved pupping events to revise reproductive rate estimates for Hawaiian monk seals in the main Hawaiian Islands - Stacie J. Robinson; Albert L. Harting; Tracy Mercer; Thea C. Johanos; Jason D. Baker; Charles L. Littnan (Marine Mammal Science, 2021)
We used sighting reports, including decades of citizen‐reported Hawaiian monk seal ( Neomonachus schauinslandi ) sightings, to describe female breeding biology and reproductive success in the main Hawaiian Islands. We first used this data set to describe the timing of events in the female reproductive cycle. We then conducted an expert review of patterns in sighting histories to detect unobserved pupping events. Finally, we estimated the age‐specific reproductive curve for female monk seals in the main Hawaiian Islands. Charting reproductive cycles showed indications of the robust condition of female monk seals in the main Hawaiian Islands; they nursed pups 12% longer than their counterparts in the Northwestern Hawaiian Islands and regained condition to molt more quickly after weaning a pup. By examining sighting histories, we were able to infer 25 unobserved pupping events that had previously gone uncounted. We accounted for additional uncertainty with a randomization procedure. After accounting for unobserved pupping events, the age‐specific reproductive rate of main Hawaiian Islands monk seals exceeded 0.70 for prime aged females (8–18 years). This is the highest reproductive rate reported for any of the Hawaiian monk seal breeding sites, illustrating the important role of the main Hawaiian Islands population in Hawaiian monk seal recovery.

Population‐level impacts of natural and anthropogenic causes‐of‐death for Hawaiian monk seals in the main Hawaiian Islands - Albert L. Harting; Michelle M. Barbieri; Jason D. Baker; Tracy A. Mercer; Thea C. Johanos; Stacie J. Robinson; Charles L. Littnan; Katie M. Colegrove; Dave S. Rotstein (Marine Mammal Science, 2021)
Identifying, assessing, and ranking the impact of individual threats is fundamental to the conservation and recovery of rare and endangered species. In this analysis, we quantify not only the frequency of specific causes‐of‐death (CODs) among Main Hawaiian Island (MHI) monk seals, but also assess the impact of individual CODs on the intrinsic growth rate, λ, of the MHI population. We used gross necropsy results, histopathology, and other evidence to assign probabilities of 11 COD types to each mortality and then used Monte Carlo sampling to evaluate the influence of each COD on λ. By right censoring realizations involving specific CODs, we were able to estimate λ (and its associated uncertainty) when CODs were selectively removed from influencing survival. Applying the analysis to all known and inferred deaths believed to have occurred 2004–2019, the CODs with the largest influence on λ were anthropogenic trauma, anthropogenic drowning, and protozoal disease. In aggregate, anthropogenic CODs had a larger effect on the growth rate than either natural or disease CODs. Possible bias associated with differential carcass detection, recovery, and COD classification are discussed.

Relationship between shock attenuation and stride length during running at different velocities - John Mercer; Jason Vance; Alan Hreljac; Joseph Hamill (European Journal of Applied Physiology, 2002)